PERILAKU GESER BALOK CASTELLATED MODIFIKASI KOMPOSIT MORTAR DENGAN PENYAMBUNG TULANGAN BAJA - , ANDINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In constructionâs development, IWF ( I Wide Flange) profiles used as one of the methods to reduce the construction cost and obtaining the economical construction design, which is done by adding the height of the beam through cutting the beamâs body in two pieces to create the beam, which is known by Castellated Beam. The advantage of castellated beams is to improve the moment capacity, as well as to overcome the web buckling and shear capacity reduction. This study intend to determine the shear behavior of castellated beams modified by mortar composite with reinforcement. This study was conducted with one specimen, which is castellated beams modified by D22 steel reinforcement and mortar composite as connector, and it dimensions are 275x75x7x5 mm. IWF span length used by the test was 780 mm. Reinforcement stiffener instalation done by welding method. The specimen used Joint and Roll as support. Load that applied to the beam were a two point loads which worked perpendicular to the beam, where the loading point at 1/3 and 2/3 of total length of the specimen. The result of this study will be compared with the study that has been done before. The result of this study indicate that castellated beams modified has maximum load of 715 KN. The collapse pattern of castellated beams modified by mortar composite and reinforcement is shear collapse pattern. It determined by the crack pattern of the specimen which got widening and propagate as the load increased. This Castellated Beam Modified compared with the study that has been done before are increased by 34.13% of castellated beam with hexagonal openings, 18.60% of castellated beams with rectangular holes, and 12.20% of castellated beam stiffnessed by angle shapes encased with mortar.